A TiNCl superconducting material that can be used for high-performance lithium-ion battery electrodes and a preparation method thereof

By using TiNCl superconducting material and forming a TiO2 cladding layer, the problems of the negative electrode material of lithium-ion battery in terms of volume strain and conductivity are solved, and the high specific capacity and high rate performance are improved, suitable for high performance lithium-ion batteries. design.

CN115911352BActive Publication Date: 2024-12-31PEKING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110939818.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-16
Publication Date
2024-12-31
Estimated Expiration
2041-08-16

AI Technical Summary

Technical Problem

Graphite, the negative electrode material of traditional lithium-ion batteries, has shortcomings in energy density, power density, cycle stability and rate performance, especially the structural reconstruction materials have large volume strain and poor electronic conductivity during the lithium embedding process, resulting in performance and service life. Restricted.

Method used

TiNCl superconducting material is used as the negative electrode material of lithium-ion batteries, and by forming a TiO2 cladding layer, the annealing conditions and atmosphere are adjusted to improve the electronic conductivity and structural stability of the material, avoid the collapse of the layered structure, and enhance the cycle stability and Specific capacity.

Benefits of technology

The specific capacity, rate performance and cycle stability of lithium-ion batteries are significantly improved. The specific capacity of the material can exceed the theoretical value and continue to increase with the charging and discharging process. The process is simple and the cost is low, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115911352B_ABST
    Figure CN115911352B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion battery electrode materials, and specifically relates to a method and modification measures for using TiNCl superconducting material as a high-performance lithium-ion battery electrode negative electrode material. The method comprises the steps of (1): preparing a superconducting material TiNCl electrode material and improving its crystallinity; and (2): oxidizing the TiNCl obtained in the step (1) to obtain a TiO2-coated TiNCl electrode material. After coating with TiO2, the structural stability of TiNCl is significantly improved. The method provided by the present invention can not only greatly improve the electronic conductivity of the negative electrode material, but also provide an embedded material capable of rapid lithium ion transmission. The combination of TiO2 and TiNCl can not only improve the rate performance and cycle stability, but also provide additional specific capacity for interfacial lithium storage. This synthesis method has simple steps, does not require special equipment and harsh reaction conditions, and is easy to prepare industrially.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery electrode materials, and in particular relates to a method and modification measures for using TiNCl superconducting material as a high-performance lithium ion battery electrode negative electrode material. Background Art

[0002] Rechargeable lithium-ion batteries have high energy density, high power density, low cost and environmental friendliness. They have been widely used in military and civilian fields such as strategic military equipment, new energy vehicles, and portable electronic devices. However, with the rapid development of my country and other countries in the world in the fields of manufacturing industry, Internet of Things, energy systems, etc., traditional lithium-ion batteries are increasingly difficult to meet actual needs in terms of energy density, power density, cycle stability and safety. Therefore, it is urgent to develop a new generation of high-performance lithium-ion batteries.

[0003] Lithium-ion batteries are mainly composed of positive electrode materials, negative electrode materials, electrolytes, current collectors and separators. The current commercial lithium-ion batteries are mainly based on the research and industrialization results of John Goodenough, Stanley Whittingham and Akira Yoshino, etc., using lithium cobalt oxide (LiCoO 2 ), lithium iron phosphate (LiFePO 4 ) and other materials as the positive electrode, lithium hexafluorophosphate (LiPF 6 ) is dissolved in propylene carbonate and ethylene carbonate as the electrolyte, and graphite material is used as the negative electrode. Compared with traditional secondary batteries such as lead-acid batteries, nickel-cadmium batteries, and nickel-metal hydride batteries, commercial lithium-ion batteries have higher open circuit voltage (higher than 3.6V), higher energy density (more than 150W h kg -I ), no memory effect and long working life. At present, the research and development of commercial positive electrode materials, electrolytes and current collectors has been relatively mature. However, graphite as a negative electrode material still has certain problems, such as its theoretical specific capacity is only 372mA hg -1 The actual specific capacity of the half-cell is 350mA hg -1 After more than 500 cycles, the capacity will decay accordingly, affecting the energy density of the battery. At the same time, the rate performance of graphite materials is poor, and the specific capacity drops significantly under large currents, making it difficult to use as fast-charging materials. In addition, the modification methods of graphite materials are relatively simple, mainly including the synthesis of high-specific-surface-area mesophase carbon microspheres and composites with other high-capacity materials. The relevant scientific research reports are far lower than other negative electrode materials, and the research and development momentum is insufficient. Therefore, in order to achieve a "double-high" lithium-ion battery with both high energy density and power density, it is necessary to explore other high-potential negative electrode materials.

[0004] The reaction mechanism of electrode materials is essentially the insertion and removal of lithium ions. According to the different ways of lithium ion insertion and removal, electrode materials can be divided into three categories: insertion type (Intercalation type), conversion type (Conversion type) and alloying type (Alloying type). Insertion type materials mostly have layered or pore structures, and lithium ions are transmitted between layers or in the pores without changing the structure of the material itself. Generally speaking, insertion type materials are conducive to the rapid diffusion of lithium ions, the material strain is small during the insertion and removal process, and theoretically have higher cycle stability. However, considering that there are theoretical limitations on the insertion of lithium, the specific capacity of this type of material is not high. Graphite, lithium cobalt oxide, and anatase titanium oxide (Anatase) are all common insertion type materials. Conversion-type and alloying-type materials undergo phase transformation during the lithium storage process to generate products such as lithium oxide, transition metal oxides or lithium alloys, so they are also called structurally reconstructed electrode materials (Structural Reorganization-Based Nanomaterialsas Anodes for Lithium-Ion Batteries: Design, Preparation, and Performance, Small2020, 16, 1902841). Transition metal oxides (TMO, TM = Fe, Co, Ni, Cu, Zn, etc.) are common conversion-type negative electrode materials with a specific capacity much higher than that of graphite negative electrodes, reaching 1000-1200 mA h g -1 , while the transition metals and Li 2 The interface of O can store lithium, thus achieving additional capacity. Silicon is a common alloying negative electrode material with a theoretical specific capacity of up to 4200mA hg -1 (Li 4.4 Si), the charging platform is as low as 0.2-0.3V (vs.Li + / Li). However, the defects of structural reconstruction materials are also very obvious. First, this type of material has a large volume strain during the lithium insertion process, such as Fe 2 O 3 The volume expansion reaches 100% after complete lithium insertion, and the volume expansion of silicon reaches 400% after complete lithium insertion. The extremely high volume strain will cause the electrode material to break and peel off during the charging and discharging process, seriously affecting its performance and service life. Secondly, the electronic conductivity and lithium ion transmission capacity of materials such as TMO and silicon are poor, which further affects their specific capacity performance. In order to improve the conductivity of structurally reconstructed materials and reduce strain, TMO or silicon and carbon materials are often compounded in laboratory research. Despite this, this type of composite method is not suitable for industrial applications: its synthesis process is complicated and the cost is high; the introduction of carbon materials increases the specific surface area, thereby consuming too much lithium source and reducing the first-cycle coulomb efficiency.

[0005] In summary, the ideal negative electrode material needs to have the low strain of embedded materials, as well as high ion transport and lithium storage capacity. Superconducting materials refer to conductor materials with zero resistance below the critical temperature, and usually have high electronic conductivity at room temperature. Common superconducting materials include multinary copper oxide superconductors, iron-based superconductors, ceramic superconductors, etc. Among them, the ternary MNX type (M=Ti, Zr, Hf; X=Cl, Br, I) superconductors are relatively easy to synthesize, with a conductivity of about 10 at room temperature. -2 mxD -1 Among them, the α-phase TiNCl has a FeOCl-type structure, which is specifically manifested as follows: the TiN with rock salt structure is cut along the (110) crystal plane, and each Ti atom is terminated by two Cl atoms. Overall, TiNCl has a two-dimensional layered structure with Cl-Cl repulsion between the layers and an interlayer spacing of approximately TiNCl can achieve lithium ion embedding. Theoretically, after complete lithium embedding, LiTiNCl is formed, and the Li atom combines with the four Cl atoms on the same plane, with a theoretical capacity of 275mA hg -1 After the combination, the interlayer Cl-Cl repulsion weakens and the interlayer spacing decreases. Therefore, TiNCl superconducting materials have the potential to be called embedded negative electrodes. However, TiNCl has poor cycle stability as a positive electrode material for lithium metal batteries. This is mainly because the repeated insertion and extraction of lithium ions will cause the collapse of the TiNCl layered structure and eventually form LiCl.

[0006] Anatase titanium oxide (TiO 2 ) As an embedded material, the theoretical specific capacity is about 335mA hg -1 , the charging voltage is about 1.7V, which can avoid irreversible side reactions at the interface between the electrode and the electrolyte during the battery charging and discharging process. 2 It is non-toxic to the environment, has low synthesis cost, and meets the needs of green energy. 2 The electronic conductivity of the material is poor, so the rate performance and cycle stability are not ideal. Laboratories often combine titanium oxide with highly conductive materials such as graphite and carbon nanotubes. Although this can improve battery performance, it is similar to the TMO modification method mentioned above and is difficult to use for commercial purposes. To this end, it is necessary to explore new titanium-based materials that have high electronic conductivity and structural stability, thereby realizing the design of "double-high" lithium-ion batteries. Summary of the invention

[0007] Based on the problems existing in the use of embedded negative electrode materials (graphite, anatase titanium oxide), structurally reconstructed negative electrode materials (transition metal oxides, silicon) and their composites in lithium-ion batteries, the present invention provides a design method for negative electrode materials for lithium-ion batteries based on TiNCl superconducting materials, which is used to improve the specific capacity, rate performance and cycle stability of electrode materials.

[0008] The purpose of the present invention is to provide a method for preparing a negative electrode material for lithium ion batteries with high electronic conductivity, high structural stability, low strain and excellent electrochemical performance at a relatively low cost and with a simple process. The preparation method provided by the present invention aims to solve the problems in current research that electrode materials (especially negative electrode materials) have poor conductivity, large volume expansion, and poor specific capacity, cycle stability and rate performance.

[0009] The present invention is implemented as follows: First, a reaction precursor for preparing a superconducting material is prepared, which can be a titanium-containing compound (reagent pure level) purchased directly, or a titanium-containing compound prepared by a synthesis method such as a sol-gel method or a coprecipitation method. The synthesized precursor needs to be sintered at 300-500°C for 2-6 hours. Then, the TiNCl superconducting material is prepared by annealing. An inert gas atmosphere needs to be introduced during the annealing process to prevent the precursor from encountering oxygen or water vapor, thereby hydrolyzing into titanium oxide. The annealing temperature is appropriately increased to 300-700°C to adjust the crystallinity of TiNCl. ​​By adjusting the ratio of inert gas, air and water vapor, a TiNCl nanomaterial uniformly coated with titanium oxide can be obtained. TiNCl itself has high electronic conductivity, and the layered structure facilitates rapid insertion and removal of lithium ions. TiO 2 The coating layer can stabilize the TiNCl layered structure, prevent structural collapse, and improve its structural stability at high potentials. Compared with the uncoated TiNCl material, the coated material still has a stable layered structure under high potential lithium deficiency, thereby achieving high specific capacity and high rate. 2 The interface with TiNCl can also store additional lithium ions, so during the cycle, the actual specific capacity of the negative electrode half-cell can exceed the theoretical specific capacity and continue to increase with the charge and discharge process.

[0010] The method for modifying a lithium-ion battery electrode material using a TiNCl superconducting material provided by the present invention comprises the following steps:

[0011] 1) Preparation of superconducting material TiNCl. ​​First, prepare the reaction precursor, which can be a directly purchased titanium-containing compound (reagent pure level) or a titanium-containing compound prepared by a synthetic method such as sol-gel method, coprecipitation method, solid phase sintering, etc. If the precursor is prepared by synthetic method, it needs to be sintered at 300-500℃ for 2-6h, and then planetary ball milling or high-energy ball milling (ball-to-material mass ratio is about 2:1) for 2.5h. Spread the titanium-containing precursor evenly in a corundum crucible or porcelain boat. In order to remove the moisture in the precursor, it is recommended to sinter in an inert atmosphere (He, Ne, Ar, N) at 80℃. 2 In an inert atmosphere or an active atmosphere (O 2 , HCl, NH 3 The amorphous TiNCl material is prepared by heating at 80-500° C. under the protection of a mixed atmosphere of one or a combination of two or more thereof. In order to improve its crystallinity, the temperature can be appropriately increased to 700° C. and the heating and cooling time can be increased.

[0012] 2) The TiNCl material obtained in step (1) is oxidized to form TiO 2 Coating layer. Oxidation treatment can be carried out by heat treatment, wet treatment, ball milling and the like. The atmosphere used in the heat treatment process should be selected under the premise of not affecting the stability of the electrode material and the conductivity of TiNCl. ​​The atmosphere during annealing can be an inert atmosphere (He, Ne, Ar, N 2 One or a combination of two or more) or an oxidizing atmosphere (O 2 And its inert atmosphere He, Ne, Ar, N 2 During the annealing process, the heating rate is 1-20℃min -1 , annealing temperature is within 800℃, and the holding time is 0.5-20h. During the wet treatment process, TiNCl and nitrate, chloride or titanium-containing inorganic salt are impregnated or stirred, and hydrothermal method can also be used to increase the intensity of the reaction, improve the conversion rate and shorten the reaction time. During the ball milling process, TiNCl is mixed with commercially available P25 or P90 titanium oxide, and planetary ball milling or high-energy ball milling (ball-to-material mass ratio is about 2:1) is performed for 2.5-3h.

[0013] Compared with the existing technology, the method designed by the present invention for modifying the electrode material of lithium-ion battery using superconducting materials has the following advantages:

[0014] Using superconducting materials for negative electrode materials greatly improves the electronic conductivity of the materials. TiNCl has a large interlayer spacing and is an embedded material, which is conducive to the rapid transmission of lithium ions, thereby greatly improving the specific capacity and rate performance of the material. 2The formation of a coating layer can effectively prevent the layer structure collapse of TiNCl during the lithium intercalation process, especially improve the structural stability of TiNCl under high potential lithium deficiency state, thereby improving the cycle stability of the material. 2 The interface formed with TiNCl can be used to store lithium and contribute additional capacity. The specific capacity of the final material can exceed the theoretical value and continue to rise with the charge and discharge process. In addition, the method designed by the present invention is relatively simple, does not involve the composite of multiphase materials, does not require expensive raw materials, special equipment or harsh production conditions, and can be used for large-scale industrial production.

[0015] Sample characterization

[0016] The sample structure information is collected using an X-ray diffractometer, the sample morphology and ultrastructure information is collected using a scanning electron microscope and a transmission electron microscope, the interaction between the sample elements is determined using an X-ray photoelectron spectroscopy, the thermal stability and component structure of the sample are collected using a thermogravimetric tester, the sample conductivity is measured using a comprehensive physical property measurement system, and the electrode performance of the sample is characterized using the Xinwei battery testing system. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A crystal structure diagram showing FeOCl-type TiNCl and anatase-type titanium oxide;

[0018] Figure 2 The present invention shows that the TiNCl and TiO 2 Coated TiNCl materials and TiO 2 X-ray diffraction pattern of the coating;

[0019] Figure 3 The present invention shows that the TiNCl and TiO 2 Coated TiNCl materials and TiO 2 Scanning electron micrograph of the coating;

[0020] Figure 4 The present invention shows that the TiNCl and TiO 2 Coated TiNCl materials and TiO 2 Transmission electron micrograph of the coating;

[0021] Figure 5 The present invention shows that the TiNCl and TiO 2 Coated TiNCl materials and TiO 2 X-ray photoelectron spectroscopy diffraction pattern of the coating layer;

[0022] Figure 6 The present invention shows that the TiNCl and TiO 2Coated TiNCl materials and TiO 2 Comparison of electronic conductivity of coating layers;

[0023] Figure 7 The present invention shows that the TiNCl and TiO 2 Coated TiNCl materials and TiO 2 Comparison chart of rate performance of coating layer;

[0024] Figure 8 The TiO prepared by the method according to the present invention is shown 2 Cycling performance diagram of coated TiNCl material under high current. DETAILED DESCRIPTION

[0025] In order to further explain the content, characteristics and practical effects of the present invention, the present invention is described in detail below in conjunction with the implementation examples. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0026] Implementation Example 1:

[0027] A method for preparing TiNCl superconducting material as negative electrode material by ammonia synthesis. 4 (about 9 mmol) was placed in a ceramic boat, covered with nickel foam, and the sample was quickly transferred to a quartz tube. Ar was introduced at room temperature and allowed to stand for 0.5 h. Then NH 3 , place for 3h; at 5℃min -1 The heating rate was raised to 400°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature. Finally, the NH 3 , purge with Ar at room temperature, and leave to stand for 0.5 h. Collect the samples and store them in a glove box.

[0028] The sample obtained after annealing is the TiNCl superconducting material. The electrochemical performance of this negative electrode material was evaluated using a CR2016 button cell. The button cell negative electrode is a metal lithium sheet with a thickness of 1 mm and a diameter of 15 mm. The positive electrode is composed of the TiNCl negative electrode material in Example 1, conductive acetylene black and binder polyvinylidene fluoride (PVDF), and the mass ratio is 8:1:1. The specific preparation process of the positive electrode is: first take 0.08g TiNCl superconducting material, 0.01g conductive acetylene black, and 0.5mL PVDF N-2 methylpyrrolidone solution (20mg mL -1), and after stirring for 12 hours, a slurry was prepared. The slurry was then coated on a copper foil with a thickness of 100 μm. It was dried in a vacuum oven at 120°C and then cut into electrode sheets with a diameter of 14 mm using a stamping die. The loading amount of active material on the positive electrode sheet was 1 to 1.5 mg cm -2 When assembling the battery, a glass fiber separator from Whatman and 1M lithium hexafluorophosphate electrolyte (the mass ratio of the solvent in the solvent is EC:DMC=1:1) were used. The assembly was performed in a glove box, and the oxygen and water vapor were both below 1ppm during assembly. The electrochemical test was performed using the CHI1000e electrochemical workstation from Shanghai Chenhua and the Neware battery test system from Newway.

[0029] Implementation Example 2:

[0030] An ammonia synthesis method combined with heat treatment to prepare TiO 2 The method of using TiNCl coated superconducting material as negative electrode material. 2mL TiCl 4 (about 18 mmol) was placed in a ceramic boat, covered with nickel foam, and the sample was quickly transferred to a quartz tube. Ar was introduced at room temperature and allowed to stand for 0.5 h. Then NH 3 , place for 3h; at 5℃min -1 The heating rate was raised to 350°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature. Finally, the NH 3 , introduce Ar at room temperature, and let stand for 0.5h. Place the obtained product on a porcelain boat, spread it evenly, cover the porcelain boat with nickel foam, and place it in an oven or muffle furnace for heating at a temperature of 80-500℃ and a heating rate of 5-10℃min -1 The temperature was kept for 6-12 hours, and then cooled naturally. The samples were collected and stored in a glove box.

[0031] This TiO 2 The electrochemical performance evaluation of the coated TiNCl superconducting material is the same as that of Example 1.

[0032] Implementation Example 3:

[0033] An ammonia synthesis method combined with heat treatment to prepare TiO 2 The coating layer is used as the negative electrode material. 1mL TiCl 4 (about 9 mmol) was placed in a ceramic boat, covered with nickel foam, and the sample was quickly transferred to a quartz tube. Ar was introduced at room temperature and allowed to stand for 0.5 h. Then NH 3 , place for 3h; at 5℃min -1 The heating rate was raised to 350°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature. Finally, the NH 3, introduce Ar at room temperature, and let stand for 0.5h. Place the obtained product on a porcelain boat, spread it evenly, cover the porcelain boat with nickel foam, and place it in an oven or muffle furnace for heating at a temperature of 500-700℃ and a heating rate of 5-10℃min -1 The temperature was kept for 6-12 hours, and then cooled naturally. The samples were collected and stored in a glove box.

[0034] This TiO 2 The electrochemical performance evaluation of the coating layer is the same as that of Example 1.

[0035] Implementation Example 4:

[0036] An ammonia synthesis method combined with a wet method to prepare TiO 2 The method of using TiNCl coated superconducting material as negative electrode material. 2mL TiCl 4 (about 18 mmol) was placed in a ceramic boat, covered with nickel foam, and the sample was quickly transferred to a quartz tube. Ar was introduced at room temperature and allowed to stand for 0.5 h. Then NH 3 , place for 3h; at 5℃min -1 The heating rate was raised to 350°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature. Finally, the NH 3 , pass Ar at room temperature, and let stand for 0.5h. Place the obtained product in a 100mL beaker, add 50mL deionized water, and stir for 6-12h. Then use deionized water and anhydrous ethanol to filter 3 times, take the filter residue, and dry it at 80℃ for 6-12h. Collect the sample and store it in a glove box.

[0037] This TiO 2 The electrochemical performance evaluation of the coated TiNCl superconducting material is the same as that of Example 1.

[0038] Implementation Example 5:

[0039] An ammonia synthesis method combined with a wet method to prepare TiO 2 The coating layer is used as the negative electrode material. 2mL TiCl 4 (about 18 mmol) was placed in a ceramic boat, covered with nickel foam, and the sample was quickly transferred to a quartz tube. Ar was introduced at room temperature and allowed to stand for 0.5 h. Then NH 3 , place for 3h; at 5℃min -1 The heating rate was raised to 350°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature. Finally, the NH 3, pass Ar at room temperature, and let stand for 0.5h. Place the obtained product in a 100mL beaker, add 50mL of 3% hydrogen peroxide solution, and stir for 6-12h. Then use deionized water and anhydrous ethanol to filter 3 times, take the filter residue, and dry it at 80℃ for 6-12h. Collect the sample and store it in a glove box.

[0040] This TiO 2 The electrochemical performance evaluation of the coating layer is the same as that of Example 1.

[0041] Implementation Example 6:

[0042] An ammonia synthesis method combined with ball milling to prepare TiO 2 The method of using TiNCl coated superconducting material as negative electrode material. 2mL TiCl 4 (about 18 mmol) was placed in a ceramic boat, covered with nickel foam, and the sample was quickly transferred to a quartz tube. Ar was introduced at room temperature and allowed to stand for 0.5 h. Then NH 3 , place for 3h; at 5℃min -1 The heating rate was raised to 350°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature. Finally, the NH 3 , pass Ar at room temperature, and let stand for 0.5h. Weigh 0.5g of the product and 0.05-0.5g of commercial P25 or P90 titanium oxide powder, place the two in an agate mortar, add a small amount of acetone to just immerse the powder, grind for 15min, put it in a ball mill, and high-energy ball mill for 4h. Then, place the mixture after ball milling in a corundum boat, and place the corundum boat in a tube furnace. During annealing, in a high-purity oxygen atmosphere, first heat at 5℃min -1 The temperature was raised to 400 °C at a rate of 100 °C and kept at this temperature for 6 h, then cooled naturally to room temperature. The samples were collected and stored in a glove box.

[0043] This TiO 2 The electrochemical performance evaluation of the coated TiNCl superconducting material is the same as that of Example 1.

[0044] Implementation Example 7:

[0045] A method for preparing TiNCl superconducting material as negative electrode material by gas phase-solid phase method. 0.6g NH 4 Cl (about 11 mmol) and 0.5 g of metallic Ti powder (about 10 mmol) were placed in different areas of a quartz tube at 300°C and 400°C, respectively, and Ar was introduced. The heating rate of the two temperature zones was 5°C min -1, keep warm for 3 hours, and cool naturally to room temperature. Place the obtained product in a 100mL beaker, add 50mL deionized water, and stir for 6-12 hours. Then use deionized water and anhydrous ethanol to filter 3 times, take the filter residue, and dry it at 80°C for 6-12 hours. Collect the samples and store them in a glove box.

[0046] The electrochemical performance evaluation of this TiNCl superconducting material is the same as that of Example 1.

[0047] Implementation Example 8:

[0048] A method for preparing TiNCl superconducting material as negative electrode material by solid phase method. 4 Cl (about 2mmol) and 1g of metallic Ti powder (about 20mmol) were placed in an agate mortar, and a small amount of acetone was added to just immerse the powder. After grinding for 15 minutes, it was transferred to a quartz tube, and the inside of the quartz tube was evacuated and sealed. The sealed quartz tube was placed in a muffle furnace at 300℃ or 400℃ and heated at a heating rate of 5-10℃min -1 , keep warm for 3-6 hours, and cool naturally to room temperature. Place the obtained product in a 100mL beaker, add 50mL deionized water and 1mL concentrated hydrochloric acid, and stir for 6-12 hours. Then use deionized water and anhydrous ethanol to filter 3 times, take the filter residue, and dry it at 80°C for 6-12 hours. Collect the samples and store them in a glove box.

[0049] The electrochemical performance evaluation of this TiNCl superconducting material is the same as that of Example 1.

[0050] Implementation Example 9:

[0051] A gas-solid phase method combined with high-energy ball milling to prepare TiO 2 The method of using TiNCl superconducting material as negative electrode material. 0.6g NH 4 Cl (about 11 mmol) and 0.5 g of metallic Ti powder (about 10 mmol) were placed in different areas of a quartz tube at 300°C and 400°C, respectively, and Ar was introduced. The heating rate of the two temperature zones was 5°C min -1 , keep warm for 3 hours, and cool naturally to room temperature. Weigh 0.5g of the product and 0.05-0.5g of commercial P25 or P90 titanium oxide powder, place the two in an agate mortar, add a small amount of acetone to just immerse the powder, grind for 15 minutes, put it in a ball mill, and high-energy ball mill for 4 hours. Then, place the mixture after ball milling in a corundum boat, and place the corundum boat in a tube furnace. During annealing, first heat at 5℃min in a high-purity oxygen atmosphere. -1The temperature was raised to 400 °C at a rate of 100 °C and kept at this temperature for 6 h, then cooled naturally to room temperature. The samples were collected and stored in a glove box.

[0052] This TiO 2 The electrochemical performance evaluation of the coated TiNCl superconducting material is the same as that of Example 1.

[0053] Implementation Example 10:

[0054] A solid phase method combined with high energy ball milling to prepare TiO 2 The method of using TiNCl coated superconducting material as negative electrode material. 4 Cl (about 2mmol) and 1g of metallic Ti powder (about 20mmol) were placed in an agate mortar, and a small amount of acetone was added to just immerse the powder. After grinding for 15 minutes, it was transferred to a quartz tube, and the inside of the quartz tube was evacuated and sealed. The sealed quartz tube was placed in a muffle furnace at 300℃ or 400℃ and heated at a heating rate of 5-10℃min -1 , keep warm for 3-6 hours, and cool naturally to room temperature. Place the obtained product in a 100mL beaker, add 50mL deionized water and 1mL concentrated hydrochloric acid, and stir for 6-12h. Then use deionized water and anhydrous ethanol to filter 3 times respectively, take the filter residue, and dry it at 80℃ for 6-12h. Weigh 0.5g of the product and 0.05-0.5g of commercial P25 or P90 titanium oxide powder, place them in an agate mortar, add a small amount of acetone to just immerse the powder, grind for 15 minutes, put it in a ball mill, and high-energy ball mill for 4 hours. Subsequently, place the mixture obtained after ball milling in a corundum boat, and place the corundum boat in a tubular furnace. During annealing, in a high-purity oxygen atmosphere, first 5℃min -1 The temperature was raised to 400 °C at a rate of 100 °C and kept at this temperature for 6 h, then cooled naturally to room temperature. The samples were collected and stored in a glove box.

[0055] This TiO 2 The electrochemical performance evaluation of the coated TiNCl superconducting material is the same as that of Example 1.

Claims

1. A method for preparing a TiNCl superconducting material for a negative electrode of a lithium ion battery, characterized in that: The steps include: Method 1: 0.6 g NH4Cl and 0.5 g Ti powder were placed in different areas of a quartz tube at 300°C and 400°C, respectively, and Ar was introduced; the heating rate of the two temperature zones was 5°C min -1 , keep warm for 3 hours, and cool naturally to room temperature; place the obtained product in a 100mL beaker, add 50mL deionized water, and stir for 6-12 hours; then filter with deionized water and anhydrous ethanol for 3 times, take the filter residue, and dry it at 80°C for 6-12 hours; Or, method 2: 0.1g NH4Cl and 1g metal Ti powder are placed in an agate mortar, a small amount of acetone is added to just immerse the powder, and after grinding for 15 minutes, it is transferred to a quartz tube, the inside of the quartz tube is evacuated and sealed; the sealed quartz tube is placed in a muffle furnace at 300℃ or 400℃ and heated at a heating rate of 5-10℃ min -1 , keep warm for 3-6 hours, and cool naturally to room temperature; place the obtained product in a 100mL beaker, add 50mL deionized water and 1mL concentrated hydrochloric acid, and stir for 6-12 hours; then use deionized water and anhydrous ethanol to filter 3 times respectively, take the filter residue, and dry it at 80°C for 6-12 hours.

2. A method for preparing a TiO2-coated TiNCl material, characterized in that: The steps include: Method 1: Place 1 mL of TiCl4 in a ceramic boat, cover the ceramic boat with nickel foam, quickly transfer the sample to a quartz tube, pass Ar at room temperature, and let stand for 0.5 h; then pass NH3 and let stand for 3 h; -1 The temperature was raised to 350°C at a rate of 100°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature; finally, the introduction of NH3 was stopped, and Ar was introduced at room temperature, and the mixture was allowed to stand for 0.5 hours; the obtained product was placed on a porcelain boat, spread evenly, and the porcelain boat was covered with nickel foam, and placed in an oven or muffle furnace for heating at a temperature of 500-700°C and a heating rate of 5-10°C min -1 , the heat preservation time is 6-12h, and then cool naturally; Or, method 2: place 2 mL of TiCl4 in a ceramic boat, cover the ceramic boat with nickel foam, and quickly transfer the sample to a quartz tube; introduce Ar at room temperature, let stand for 0.5 h, then introduce NH3, let stand for 3 h; -1 The heating rate was raised to 350°C and kept at this temperature for 3 hours, and then naturally cooled to room temperature; finally, the introduction of NH3 was stopped, and Ar was introduced at room temperature, and the mixture was allowed to stand for 0.5 hours; 0.5 g of the product and 0.05-0.5 g of titanium oxide powder were weighed, and the two were placed in an agate mortar, and a small amount of acetone was added to just immerse the powder. After grinding for 15 minutes, the mixture was placed in a ball mill and subjected to high-energy ball milling for 4 hours; then, the mixture obtained after ball milling was placed in a corundum boat, and the corundum boat was placed in a tube furnace. During annealing, the mixture was first heated at 5°C min in a high-purity oxygen atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and kept at this temperature for 6 h, and then naturally cooled to room temperature; Or, method 3: 0.6 g NH4Cl and 0.5 g Ti powder were placed in different areas of a quartz tube at 300 °C and 400 °C, respectively, and Ar was introduced; the heating rate of the two temperature zones was 5 °C min -1 , keep warm for 3 hours, and cool naturally to room temperature; weigh 0.5g of the product and 0.05-0.5g of titanium oxide powder, put the two in an agate mortar, add a small amount of acetone to just immerse the powder, grind for 15 minutes, put it in a ball mill, and high-energy ball mill for 4 hours; then, put the mixture obtained after ball milling in a corundum boat, and put the corundum boat in a tube furnace; when annealing, first heat it at 5℃min in a high-purity oxygen atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and kept at this temperature for 6 h, and then naturally cooled to room temperature; Or, method 4: 0.1g NH4Cl and 1g metal Ti powder are placed in an agate mortar, a small amount of acetone is added to just immerse the powder, and after grinding for 15 minutes, it is transferred to a quartz tube, the inside of the quartz tube is evacuated and sealed; the sealed quartz tube is placed in a muffle furnace at 300℃ or 400℃ and heated at a heating rate of 5-10℃ min -1 , keep warm for 3-6h, and cool naturally to room temperature; place the obtained product in a 100mL beaker, add 50mL deionized water and 1mL concentrated hydrochloric acid, and stir for 6-12h; then use deionized water and anhydrous ethanol to filter 3 times respectively, take the filter residue, and dry it at 80℃ for 6-12h; weigh 0.5g of the product and 0.05-0.5g of titanium oxide powder, put the two in an agate mortar, add a small amount of acetone to just immerse the powder, grind for 15min, put it in a ball mill, and high-energy ball mill for 4h; then, place the mixture obtained after ball milling in a corundum boat, and place the corundum boat in a tube furnace; when annealing, in a high-purity oxygen atmosphere, first at 5℃ min -1 The temperature was raised to 400 °C at a rate of 100 °C and kept at this temperature for 6 h, followed by natural cooling to room temperature.

3. Application of a TiNCl superconducting material prepared by the method for preparing a TiNCl superconducting material for a lithium ion battery negative electrode according to claim 1, or a TiO2-coated TiNCl material prepared by the method for preparing a TiO2-coated TiNCl material according to claim 2 in a lithium ion battery negative electrode, a lithium ion battery positive electrode, a lithium metal battery, a supercapacitor, a sodium ion battery, a zinc ion battery, or a photocatalyst.